Si VII/Mg VII and Si IX/Mg IX LINE DIAGNOSTICS for SOLAR PLASMA - Mohan A.; Dwivedi B.N. (My University, 2025)
New calculations for Si vii/Mg vu and Si ix/Mg IX theoretical line ratios as a tool for plasma density diagnostics and for the estimation of relative element abundance in the solar atmosphere are presented, making use of the EUV spectrum of an active region obtained by the Solar EUV Rocket Telescope and Spectrograph (SERTS). Theoretical line ratios, hitherto not observed, are discussed for diagnosing solar plasma from the observations obtainable with the Coronal Diagnostic Spectrometer (CDS) instrument on board the SOHO mission. © 1996 Kluwer Academic Publishers.